Orthotopic Heart Transplant Recipient Presenting with Sudden Onset Homonymous Hemianopia - Chawnchhim, Abraham L.; Sharma, Neha; Goel, Chetna; Mahajan, Charu (Journal of Neuroanaesthesiology and Critical Care, 2023)
Infectious complications are common among heart transplant recipients due to immune suppressive therapy mandatorily given to prevent organ rejection. We share our experience regarding an orthotopic heart transplant recipient who underwent craniotomy and evacuation of intracerebral abscess under general anesthesia in our operation theater. An orthotopic heart transplant recipient presented with headache, fever, and left-sided homonymous hemianopia. Noncontrast computed tomography (NCCT) of the head showed a right occipital space-occupying lesion suggestive of an abscess. Craniotomy and evacuation of abscess was successfully performed under general anesthesia. There are several concerns pertinent to orthotopic heart transplant recipients mainly due to denervated heart status and immune suppressive therapy, which poses perioperative challenge. We report successful anesthetic management of this case.
Keywords: orthotopic heart transplant recipient; cerebral abscess; homonymous hemianopia; craniotomy